Selection of Curricular Topics Using Framework for Enhanced Quality Function Deployment - Soota, Tarun; Singh, Harvendra; Mishra, R C (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> 0 false 18 pt 18 pt 0 0 false false false <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman";} @page Section1 {size:8.5in 11.0in; margin:1.0in 1.25in 1.0in 1.25in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> <!--StartFragment--> Based on the fact that products and services require an interdisciplinary approach, there is a growing conviction that engineering disciplines are converging rather than diverging. The curricula must, therefore, be designed to ensure that a student will posses all the qualities of a generalist and all the competence of a specialist with a capacity for life long learning. Decision science can be an effective tool for enhancing organizational participation during strategic and complex decision making. The challenge was to develop a set of curricular topics that not only directly contributed to the identified goals but that did so proportionately to the respective importance level of each goal. This paper describes an application of Quality Function Deployment (QFD) to define curricular topics that meet program objectives. The inputs for the QFD’s were obtained through several brainstorming sessions of students, faculty members, administrators, and business people. Based on the ability of QFD to establish relationships, the model identifies the most important topics and quantifies their impact on meeting program goals. The model was developed to support restructuring of a masters of technology programme. It provides a framework using enhanced quality function deployment for selection of curricular topics. The model provided a practical methodology for developing faculty consensus in the selection of curricular topics with a strategic focus. The decision problem is structured for assessment of impact of curricular topics on the program goals keeping checks on consistencies. <!--EndFragment-->